THE GOSPEL IN ASIA - Padinjarekuttu, Isaac (Asian Horizons, 2011)
In this brief historical sketch, I would like to draw your attention to some of the less remembered facts and events in the history of the missions in Asia. The evangelisation of Asia did not begin with St Francis Xavier. It did not begin during the Vasco da Gama era. It began on that glorious day when Christ came on the shores of the Sea of Galilee announcing, “The kingdom of God is at hand; repent, and believe in the Gospel” (Mk1:15). It took another step forward when he sent out his disciples two by two saying, “Preach as you go… Heal the sick, raise the dead…You received without paying, give without pay” (Mt 10:7-9).